1998
DOI: 10.1080/02652039809374681
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Canadian human blood plasma for ochratoxin A

Abstract: Blood plasma samples collected from 144 healthy volunteers in 16 locations across Canada in 1994 were analysed for ochratoxin A (OTA). The method of analysis included cleanup by C18 solid phase extraction and immunoaffinity columns followed by liquid chromatography (LC) with fluorescence detection, which gave 86.5% (s.d. = 9.7) recovery (n = 31) of OTA (added at 2 ng/ml) with a detection limit of 0.15 ng/ml. The arithmetic mean concentration found in the plasma samples, corrected for volume of anticoagulant ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…Studies surveying the OTA content of human blood samples have been performed in numerous countries of the world including Hungary, and such surveys have invariably detected a high rate of positivity (BreitholtzEmanuelsson et al, 1993;Kovács et al, 1995;Solti et al, 1997;Scott et al, 1998;Özcelik et al, 2001). In addition to the OTA contamination of human blood samples, the occurrence of ochratoxin in human colostrum has also been reported (Breitholtz-Emanuelsson et al, 1993;Kovács et al, 1995).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
“…Studies surveying the OTA content of human blood samples have been performed in numerous countries of the world including Hungary, and such surveys have invariably detected a high rate of positivity (BreitholtzEmanuelsson et al, 1993;Kovács et al, 1995;Solti et al, 1997;Scott et al, 1998;Özcelik et al, 2001). In addition to the OTA contamination of human blood samples, the occurrence of ochratoxin in human colostrum has also been reported (Breitholtz-Emanuelsson et al, 1993;Kovács et al, 1995).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
“…In a survey of human blood plasma in Canada, there was 100% incidence of OTA and a statistically significant greater mean concentration of OTA in samples from Winnipeg than in samples from Toronto, Vancouver and Saint John, New Brunswick (Scott et al 1998). In Switzerland, also with 100% incidence, men living south of the Alps had higher mean and median OTA concentrations in serum than men who lived north of the Alps (Zimmerli & Dick 1995).…”
Section: Regional Differences In Human Blood Concentration Of Ochratomentioning
confidence: 99%
“…Several studies -in Canada (Frohlich et al 1991, Scott et al 1998, Lebanon (Assaf et al 2004), Japan (Ueno et al 1998), Norway (Skaug 2003), Germany (Gareis et al 2000), northern Spain (Jiménez et al 1998), Italy (Tuscany) (Palli et al 1999) and Tunisia ) -found no difference with age in positive levels of OTA in human blood (adults). However, in a UK dietary exposure study (Gilbert et al 2001), plasma concentrations of OTA did appear to depend on age, with higher levels in 30-44 year-olds compared to <30 year-olds and >45 year-olds and this was significant for a screening sample taken 30 days before the start of the study.…”
Section: Ochratoxin a In Human Blood And Agementioning
confidence: 99%
See 2 more Smart Citations